2015
DOI: 10.4037/ccn2015232
|View full text |Cite
|
Sign up to set email alerts
|

Making It Meaningful: Finding Quality Improvement Projects Worthy of Your Time, Effort, and Expertise

Abstract: This article is the second of a 4-part quality improvement resource series for critical care nurses interested in implementing system process or performance improvement projects. The article is a brainstorming session on paper, written to assist nurses and managers in identifying possible quality improvement projects that are meaningful to them and will make a real difference in their critical care units. Every unit and institution has its own unique mix of resources, culture, physical environment, patient pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…An early win for the team not only encourages them to continue but can help gain buy-in from leadership and staff. 3,14 In our pressure injury example, the team noted that all stage 3 pressure injuries were injuries to the ears and had been caused by respiratory equipment. 28 Although ear injuries were not represented in the "vital few," their severity was a concern.…”
Section: Pareto Chartmentioning
confidence: 99%
See 3 more Smart Citations
“…An early win for the team not only encourages them to continue but can help gain buy-in from leadership and staff. 3,14 In our pressure injury example, the team noted that all stage 3 pressure injuries were injuries to the ears and had been caused by respiratory equipment. 28 Although ear injuries were not represented in the "vital few," their severity was a concern.…”
Section: Pareto Chartmentioning
confidence: 99%
“…Improving clinical practice and sustaining those improvements require leadership support from all levels within the organization. 3 Once the team has been assembled, it should thoroughly assess the problem or quality issue. When problems occur in the workplace-either as a clinical issue, such as an increase in the number of medication errors, or as a need for improvement, such as a change in workflow-health care workers often want to identify the cause and remedy the situation quickly.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that health care efficiency can be improved and cost can be decreased through programs in which nurses learn to understand and apply evidence-based practice (EBP) and QI processes. [2][3][4] However, although EBP and QI programs may include sound tools, these programs generally have less emphasis in the theory and practice of implementing change.…”
mentioning
confidence: 99%